Design of Development Environment for Embedded Control Software Based on Simulink - DAI Jisheng; CHEN Junbo; LI Cheng; LI Yi (Kongzhi Yu Xinxi Jishu)
It analyzed the problems which existed in traditional control software development methods, designed a development environment for embedded control software based on Simulink, and explained the key technologies such as automatic code generation, device driver integration, automatic compilation and downloading in the design. Based on the development environment, using the model-based design concept, it effectively solves such problems as low efficiency and long cycle in the traditional method.